Generalized Mathematical Model of Controlled Linear Oscillating Mechatronic Device - Senulis, A.; Eidukas, D.; Guseinoviene, E. (Elektronika ir Elektrotechnika, 2011)
This paper presents the general mathematical model of double-sided splingless linear oscillating mechatronic device – oscillating motor- ompressor which is supplied by thyristor voltage converter. The model presents possibilities to evaluate losses of the windings and losses in the magnetic circuit, nonlinear inductances, mutual inductances, special current feedback using harmonic analysis for the control, oscillations not only of the moving part, but also the “stator” oscillations. Also using this model such parameters can be calculated – oscillation centre drift, oscillating coordinates and velocities of mover and stator, all currents and voltages, electromagnetic force, harmonics of each time-dependent parameter. Ill. 7, bibl. 13 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.108.2.145